KEUNTUNGAN PEMBESARAN SAPI PERANAKAN SIMMENTAL MELALUI PERBAIKAN PAKAN DI KABUPATEN SEMARANG - Dewi Sahara; Muryanto ,; Subiharta , (Jurnal Pengkajian dan Pengembangan Teknologi Pertanian, 2015)
ABSTRACT Profit of Fattening on Simmental-Crossed Breed Cattles through to Feed’s Improvement in Semarang Regency, Central Java. Most of cattle management in Central Java is traditional farms with low meat production. One of the efforts to increase meat production is improvement of feed formulation for calves. This study aimed to determine the average daily gains (ADG) and profitability of cattle rearing with the improvement of feed formulation compared to the traditional one by farmers. The study was conducted in the Polosiri village, Bawen sub-district, Semarang regency from October to December 2012. A total of sixteen heads of Simmental-crossed breed of 6-8 months old were divided into two groups: one group was given feed improvement (elephant grass, fermented rice straw and concentrates) and another with farmer's feed formulation (elephant grass, rice straw, cassava and rice bran). ADG was calculated by subtracting the initial weight from the final weight divided by the period of rearing. The profit was calculated by financial feasibility using Benefit and Cost Ratio (BCR) formula, meanwhile, the difference of profit between two group was calculated by Marginal Benefit and Cost Ratio (MBCR). The results showed that ADG from feed improvement model was 0.66 + 0.17 kg/head/day which is higher than the farmer's feed models that accounted for 0.43 + 0.39 kg/head/day. The BCR analyses for feed improvement model and farmer’s model were 0.13 and 0.09, respectively, with the profit of Rp7.733.500 and Rp4.999.650, respectively. Different feeding model yielded MBCR value of 1.40. It can be concluded that fattening on Simmental-crossed breed cattle with feed improvement model in the form of elephant grass, fermented rice straw, and concentrates is able to improve ADG. Keywords: fattening, feed improvement, gain, profit  ABSTRAK Usaha peternakan sapi di Jawa Tengah merupakan usaha ternak sapi rakyat dengan sistem pemeliharaan tradisional sehingga produktivitas daging rendah. Salah satu upaya untuk meningkatkan produksi daging sapi ialah membesarkan pedet melalui perbaikan pakan. Pengkajian dilaksanakan dengan tujuan mengetahui Pertambahan Bobot Badan Harian (PBBH) dan keuntungan usaha pembesaran sapi yang mendapatkan perbaikan pakan dibandingkan pakan model peternak. Pengkajian dilakukan di Desa Polosiri, Kecamatan Bawen, Kabupaten Semarang, dari bulan Oktober–Desember 2012, menggunakan 16 ekor sapi peranakan Simmental umur 6–8 bulan yang dibagi menjadi dua kelompok, yaitu kelompok yang mendapatkan perbaikan pakan (rumput gajah, jerami fermentasi dan konsentrat dengan jumlah sesuai dengan bobot badan) dan kelompok model peternak (rumput gajah, jerami, ubi kayu dan bekatul.  PBBH dihitung dengan mengurangi bobot badan akhir dan bobot badan awal dibagi waktu pembesaran. Keuntungan didekati dengan kelayakan finansial usaha dianalisis dengan membandingkan keuntungan dan biaya (BCR) dan rasio perubahan keuntungan dan biaya (MBCR). Hasil kajian menunjukkan bahwa PBBH pada pembesaran anak sapi yang mendapat perlakuan perbaikan pakan sebesar 0,66 + 0,17 kg/ekor/hari lebih tinggi dibandingkan model peternak 0,43 + 0,39 kg/ekor/hari. Hasil analisis BCR memperoleh nilai 0,13 dan 0,09 untuk pemberian pakan  perbaikan dan pakan peternak dengan keuntungan masing-masing Rp7.733.550 dan Rp4.999.950. Perbedaan pemberian pakan menghasilkan nilai MBCR = 1,40. Dapat disimpulkan bahwa pembesaran sapi peranakan Simmental dengan pemberian pakan perbaikan berupa rumput gajah, jerami fermentasi dan konsentrat mampu meningkatkan PBBH. Kata kunci: Pembesaran pedet, pakan perbaikan, bobot badan, keuntungan